Systematic characterization of gastrointestinal clinical trials. Issue 5 (May 2016) - Espinoza, Magdalena; Hsieh, Antony; Hsiehchen, David
Abstract: Background: Clinical guidelines are commonly based on inadequate evidence, suggesting deficiencies in the present portfolio of clinical research. Aims: To investigate characteristics of clinical trials examining gastrointestinal (GI) diseases registered in ClinicalTrials.gov. Methods: A cross-sectional analysis of 13, 647 GI trials and 111, 535 non-GI trials initiated between January 1997 and September 2013 was performed. Entries were sorted by operational status, purpose, interventions, trial design, and epochs to identify trends and interactions in trial properties. Results: The global production of GI trials has remained static in recent years and a majority of research efforts are focused on a few diseases. While GI trials are generally produced by highly populated US states and countries, they are also seldom larger than 500 patients. The likelihood of using data monitoring committees, randomization, and double blinding in GI trials has increased over time, though a substantial fraction of GI trials still do not employ rigorous trial designs. While levels of GI trials correlate with disease burden, the explained variance of GI trials by disease burden worldwide is poor. Conclusion: GI trials are chiefly concentrated in few diseases and highly populated regions, exhibit heterogeneous trends and methodologies, and are sensitive to disease burdens, though more so within North America than worldwide.